The Effect of Audit Quality on the Market Value of Cash Holdings: Evidence from Tehran Stock Exchange and IACPA - Moslem Tahmasbi; Hesam Rahmani; Mohammad Bakhtiarvand (International Journal of Management, Accounting and Economics, 2020)
In this study, the effect of audit quality on the market value of cash holdings was investigated. The company’s auditor expertise and tenure were considered as measures of audit quality. The regression model developed by Faulkender and Wang (2006) was applied to estimate the market value of cash holdings.Target sample includes 175 listed companies in the Tehran Stock Exchange during 2008-2014 (1387-1393Iranian calendars). In this study, it was supposed that audit quality affects the market value of cash holdings. The hypotheses were examined using panel data and a multivariate regression model of generalized least squares. The results indicated that the company’s auditor expertise affects the market value of cash holdings (the positive and significant relationship statistically). However, tenure does not affect the market value of cash holdings.